ORIENTATION AND IMPROVEMENT OF EDUCATION OF STAFF FOR SUSTAINABLE DEVELOPMENT OF AGRICULTURE AND ENVIRONMENT PROTECTION - Ivanc, Aleksandar; Bošković, Jelena; Simić, Jeremija; Hojka, Zdravko; Sarić, Mirko (Economics of Agriculture, 2006)
Authors of this paper research necessaries of orientation and improvement of education of staff for purpose of sustainable development of agriculture and environment protection. According with global questions of education improvement, this paper especially realizes basis and aims of high education in function of orientation sustainable development agriculture and environment protection. In addition, it point was on role of highly professional staff in function of abetment of development organic agriculture and healthy safe food production on familys husbandry and farm economies. Improvement of education highly professional agricultural staff in our country is connected with Bologna declaration demands and developing of Bologna process in Europe. From this point education of agricultural staff, we must have in mind facts that European market will become unique market for students and professors.